Social media use and various factors affecting indonesian mental health during the COVID-19: A pathway to remember - Tarnoto, Nissa; Yuniawati, Rudy; Wijayati, Rifky Dora; Herdian, Herdian (Intelektual Pustaka Media Utama, 2023)
In the middle of the COVID-19 pandemic, Indonesia is experiencing a crisis in mental health, and it appears that social media is making the issue much worse. This study examines the impact of social media use and its elements on Indonesians' mental health as a first step towards identifying potential disasters. The study uses a convergent mixed methods approach, utilizing both quantitative data measured by social networking activity intensity scale (SNAIS) and general anxiety disorder 7 scale (GAD-7), and qualitative data collected through open-ended questions answered by 347 Indonesians aged 17-65 years old. The results indicate a significant link (p<0.05) between excessive social media use during the pandemic and unfavorable impacts on users' mental health, specifically the development of anxiety. The study also finds that hoaxes and rumors on social media about COVID-19 infections, inadequate health facilities, and the Indonesian government's slow response contributed to the population's uneasiness. According to the studies, social media literacy is needed to managing social media use during times of crisis. This study adds to the social media-mental heath literature. It illuminates Indonesians' challenges, providing insights that might improve public health policies, mental health therapies, and educational efforts to encourage good social media practises.